2018
DOI: 10.1002/ange.201711964
|View full text |Cite
|
Sign up to set email alerts
|

Fuel‐Selective Transient Activation of Nanosystems for Signal Generation

Abstract: The transient activation of function using chemical fuels is common in nature,but muchl ess in synthetic systems. Progress towards the development of systems with acomplexity similar to that of natural ones requires chemical fuel selectivity. Here,weshowthat aself-assembled nanosystem, composed of monolayer-protected gold nanoparticles and af luorogenic peptide,isactivated for transient signal generation only in case the chemical fuel matches the recognition site present at the nanoparticle surface.Amodificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The difficulty in implementing such a concept in synthetic system is related to the need for highest levels of programmability and ability for deterministic autonomous reconfiguration leading to multiple transient dynamic steady-state (DySS) structures, which is a profound challenge in supramolecular chemistry. [24][25][26] On the contrary, DNA shows great potential to program reaction networks and pathways for self-assemblies in a systems chemistry approach. [27][28][29] Herein, we demonstrate pathway complexity in ATP-fueled transient DNA polymerizations from a species pool realizing autonomous and transient multiple DySS structures (Figure 1a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in implementing such a concept in synthetic system is related to the need for highest levels of programmability and ability for deterministic autonomous reconfiguration leading to multiple transient dynamic steady-state (DySS) structures, which is a profound challenge in supramolecular chemistry. [24][25][26] On the contrary, DNA shows great potential to program reaction networks and pathways for self-assemblies in a systems chemistry approach. [27][28][29] Herein, we demonstrate pathway complexity in ATP-fueled transient DNA polymerizations from a species pool realizing autonomous and transient multiple DySS structures (Figure 1a,b).…”
Section: Introductionmentioning
confidence: 99%
“…AP cleaves monophosphate nucleosides in nucleoside and inorganic phosphate, which have a lower templating ability. 27,32 Consequently, the addition of nucleotide under dissipative conditions installed by the presence of enzyme results in templated self-assembly with a lifetime that is determined by the rate at which the template is cleaved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nanozymes are functional nanomaterials with emerging enzyme-like activities. Because of their much more stable catalytic activities and lower cost compared with those of natural enzymes, they have recently been developed for wide applications, including biosensing. A few pioneering studies have shown that the nanozyme sensor arrays composed of gold or iron oxide nanoparticles could be used for protein discrimination. Inspired by these, we envisaged that 2D-MOF nanozymes are good alternatives to gold or iron oxide nanoparticles for sensor arrays because of their tailorable structures and catalytic activities as well as their highly exposed surfaces and active sites . In this work, we demonstrated that the peroxidase-mimicking activities of a series of 2D-MOF nanozymes could be modulated by various phosphates, forming the basis of the designed sensor arrays for phosphate discrimination.…”
mentioning
confidence: 99%